2005
DOI: 10.1271/bbb.69.1914
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Novel Aminoacylase fromStreptomyces mobaraensis

Abstract: A novel aminoacylase was purified to homogeneity from culture broth of Streptomyces mobaraensis, as evidenced by SDS-polyacrylamide gel electrophoresis (PAGE). The enzyme was a monomer with an approximate molecular mass of 100 kDa. The purified enzyme was inhibited by the presence of 1,10-phenanthroline and activated by the addition of Co2+. It was stable at temperatures of up to 60 degrees C for 1 h at pH 7.2. It showed broad substrate specificity to N-acetylated L-amino acids. It catalyzed the hydrolysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
1
13
0
Order By: Relevance
“…Displaying an identity percentage of 97%, the selected Streptomyces isolate St62 was identified as Streptomyces minutiscleroticus. Some previously studied Streptomyces isolates were reported to have enzymes with quorum quenching abilities like the study carried out by Park and coworkers (Park et al, 2005)and Streptomyces mobaraensis in the study of Koreishi and coworkers (Koreishi et al, 2005), however, the isolate in this study appears to be the first identified quorum quenching Streptomyces of this type.…”
Section: Discussionmentioning
confidence: 60%
“…Displaying an identity percentage of 97%, the selected Streptomyces isolate St62 was identified as Streptomyces minutiscleroticus. Some previously studied Streptomyces isolates were reported to have enzymes with quorum quenching abilities like the study carried out by Park and coworkers (Park et al, 2005)and Streptomyces mobaraensis in the study of Koreishi and coworkers (Koreishi et al, 2005), however, the isolate in this study appears to be the first identified quorum quenching Streptomyces of this type.…”
Section: Discussionmentioning
confidence: 60%
“…It should be noted here that the culture supernatant contained some other enzymes in addition to Sm-AA that might have hydrolyzed N-acetyl-L-Met, such as aminoacylase, reported in our previous paper. 14) Therefore, the amount of wild-type Sm-AA in the culture supernatant discussed above was evaluated from the N-lauroyl-L-Met hydrolyzing activity of the culture supernatant (0.47 U/ml) with the specific activities measured for the purified enzyme towards N-acetyl-LMet (440 U/mg) and N-lauroyl-L-Met (65 U/mg). No activity was detected when wild-type S. lividans cells or those harboring pSH19 were used.…”
Section: Resultsmentioning
confidence: 99%
“…The enzyme properties of Sm-AA were studied primarily using purified recombinant Sm-AA at a final concentration of 1.5 mg/ml by a method similar to that reported in our previous work. 14) When wild-type Sm-AA was used, its final concentration was usually 0.4 mg/ml.…”
Section: Construction Of the Expression Plasmidmentioning
confidence: 99%
“…Lipases are the most currently used enzymes to synthesize bioactive molecules, but their use involves the utilization of organic solvent as reaction medium. These enzymes are able to catalyze the acylation of amino acids or peptides with fatty acids in aqueous media [1,[8][9][10][11][12]. Studies reported the use of neoteric media such as ionic liquids, allowing the improvement of the solubility of peptides such as Lys-Ser in 1-butyl-3-methylimidazolium hexafluorophosphate ([Bmim] + [PF6] − ) in comparison with 2-methyl-2-butanol and of the reaction performances [6].…”
Section: Introductionmentioning
confidence: 99%